Physical fitness before and during the COVID-19 pandemic: Results of annual national physical fitness surveillance among 16,647,699 Japanese children and adolescents between 2013 and 2021 - Tetsuhiro Kidokoro; Grant R. Tomkinson; Justin J. Lang; Koya Suzuki (Elsevier, 2023)
Background: Limited nationally representative evidence is available on temporal trends in physical fitness (PF) for children and adolescents during the coronavirus disease 2019 (COVID-19) pandemic. The primary aim was to examine the temporal trends in PF for Japanese children and adolescents before and during the COVID-19 pandemic. The secondary aim was to estimate the concurrent trends in body size (measured as body mass and height) and movement behaviors (exercise, screen, and sleep time). Methods: Census PF data for children in Grade 5 (aged 10-11 years) and adolescents in Grade 8 (aged 13-14 years) were obtained for the years 2013-2021 from the National Survey of Physical Fitness, Athletic Performance, and Exercise Habits in Japan (n = 16,647,699). PF and body size were objectively measured, and movement behaviors were self-reported. Using sample-weighted linear regression, temporal trends in mean PF were calculated before the pandemic (2013-2019) and during the pandemic (2019-2021) with adjustments for age, sex, body size, and exercise time. Results: When adjusted for age, sex, body size, and exercise time, there were significant declines in PF during the pandemic, with the largest declines observed in 20-m shuttle run (standardized (Cohen's) effect size (ES) = −0.109 per annum (p.a.)) and sit-ups performance (ES = −0.133 p.a.). The magnitude of the declines in 20-m shuttle run and sit-ups performances were 18- and 15-fold larger, respectively, than the improvements seen before the pandemic (2013-2019), after adjusting for age, sex, body size, and exercise time. During the pandemic, both body mass and screen time significantly increased, and exercise time decreased. Conclusion: Declines in 20-m shuttle run and sit-ups performances suggest corresponding declines in population health during the COVID-19 pandemic.